ANTECEDENT FACTORS OF VOCATIONAL HIGH SCHOOL STUDENTS' READINESS FOR SELECTING CAREERS: A CASE IN INDONESIA - Tuatul Mahfud; Ibnu Siswanto; Danar Susilo Wijayanto; Putu Fajar Puspitasari (Jurnal Cakrawala Pendidikan, 2020)
Vocational graduates' readiness for selecting careers is an important topic for vocational education research. Although there have been many studies on vocational student career selection readiness, there are only few studies on the roles of teaching quality, social capital, and psychological capital in shaping vocational students' readiness for selecting careers. This study aims to examine the antecedent factors of high school students' readiness for career selection which involve teaching quality, psychological capital, and social capital factors. This study employed the quantitative approach with ex-post facto design. The data were randomly collected from 279 vocational high school students in North Lampung-Indonesia by means of online questionnaires. SEM analysis was carried out in this study to see the effects among variables. The results show that readiness for selecting careers is influenced by teaching quality and psychological capital, as social capital does not directly influence student readiness. Besides, psychological capital is influenced by teaching quality and social capital. Then, social capital is influenced by teaching quality. Social and psychological capitals together mediate the effect of teaching quality on the readiness for selecting careers. The research findings present some implications for vocational education practitioners wishing to make further improvements.